2018
DOI: 10.1159/000494786
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA HOXA-AS2 Promotes Papillary Thyroid Cancer Progression by Regulating miR-520c-3p/S100A4 Pathway

Abstract: Background/Aims: Thyroid cancer is one of the most prevalent endocrine tumors. The present study examined the effects of lncRNA HOXA cluster antisense RNA2 (HOXA-AS2) on the progression of papillary thyroid cancer (PTC), and explored the underlying molecular mechanisms. Methods: Quantitative real-time PCR was used to detect HOXA-AS2, miR-520c-3p and S100 calcium-binding protein A4 (S100A4) expression. Furthermore, the effects of HOXA-AS2 silencing and overexpression on cell proliferation, migration, and invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…In the end, 12 articles with a total of 796 patients (Table 1) were included in this study. There were 8 types of cancer in these 12 literatures, including 2 cases of lung cancer [17,18], 2 of thyroid cancer [19,20], 1 of bladder cancer [21], 1 of breast cancer [22], 1 of gastric cancer [23], 2 of colorectal cancer [9,10], 1 of osteosarcoma [24] and 2 cases of liver cancer [14,25]. All the 12 articles come from China (Table 1).…”
Section: Incorporate the Results Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In the end, 12 articles with a total of 796 patients (Table 1) were included in this study. There were 8 types of cancer in these 12 literatures, including 2 cases of lung cancer [17,18], 2 of thyroid cancer [19,20], 1 of bladder cancer [21], 1 of breast cancer [22], 1 of gastric cancer [23], 2 of colorectal cancer [9,10], 1 of osteosarcoma [24] and 2 cases of liver cancer [14,25]. All the 12 articles come from China (Table 1).…”
Section: Incorporate the Results Of The Studymentioning
confidence: 99%
“…Through the lnCAR database, we found that HOXA-AS2 can regulate the expression of mRNA through miR-372-3p, miR-373-3p, miR-302a-3p, miR-519d-3p, miR-106b-5p, miR-520b, miR-302e, miR-520e, miR-106a-5p, miR-302d-3p, miR-302c-3p, MiR-302b-3p, miR-20a-5p, miR-520d-3p, miR-17-5p, miR-93-5p, miR-20b-5p, miR-520c-3p and miR-520a-3p, and further participate in the occurrence and development of tumor. At present, studies have confirmed that long-chain non-coding RNAHOXA-AS2 can take part in the progression of AML, thyroid papillary carcinoma, HCC and breast cancer throuh target regulating of miR-520c-3p [12,14,19,22]. In addition, HOXA-AS2 can promote the malignant progression of non-small cell lung cancer, thyroid papillary carcinoma and liver cancer through miRNA-216a-5p, miR-520a-3p, miR-15a-5p and miR-125b [17,18,20,21].…”
Section: Publication Bias and Sensitivity Analysismentioning
confidence: 99%
“…Moreover, several studies revealed the roles of lncRNAs in the regulation of PTC progression. For example, Xia et al (33) reported that lncRNA HOXA-AS2 was upregulated in PTC tissues and promoted migration and invasion of PTC cells by regulating the miR-520c-3p/S100A4 pathway. Wang et al (34) demonstrated that LINC01186 suppressed proliferation and invasion of PTC cells by decreasing the expression of YAP1 and increasing LATS1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Mechanistically, lncRNAs could act as miRNA spongers to modulate miRNA downstream mRNA via ceRNA network. 34,35 miR-1301-3p has been reported to inhibit cell proliferation, induce cell apoptosis, and regulate cell-cycle progression via directly targeting ICT1 in breast cancer. 36 miRNA-1301 directly targets to N-Ras and inhibits glioma cell proliferation.…”
Section: Discussionmentioning
confidence: 99%